Screen Time and Its Impact on Physical Fitness in Children: A Cross-Sectional Study - Dwi Purwantini; Martha Sri Astuti (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2026)
Introduction: Rapid advances in digital technology have led to an increase in screen time among children, which is thought to affect their physical activity. However, the direct relationship between screen time and physical capacity in children still needs to be studied further Objectives: This study aims to determine the relationship between screen time duration and physical activity in children aged 10-11 years Methods: This study used a cross-sectional design with a sample of 44 children aged 10-11 years. Physical capacity was measured using the Incremental Shuttle Walk Test (ISWT), while screen time duration was obtained through questionnaires. Spearman's correlation analysis was used to test the relationship between variables Results: This study showed no significant relationship between screen time duration and children's physical capacity as measured by the Incremental Shuttle Walk Test (ISWT) with a correlation coefficient of 0,76 dan p=0,625 Conclusions: High screen time does not have a direct impact on children's physical capacity in the context of this study. However, it is important to continue to encourage adequate physical activity in order to maintain children's health and fitness optimally